Collaboration nation [group software]. - Goldstein, H. (IEEE spectrum)
As group software assumes a major role in the workplace, will engineers stop talking to each other? Communication is the essence of collaboration, and increasingly communication about semiconductor design is happening over the Internet not only through e-mail and threaded discussion boards, but also through specially designed Web collaboration software that lets engineers work on parts of the same chip simultaneously, whether they are down the hall or across the world. The increasing use of collaborative software has raised concerns that the engineering workplace would suffer from diminished human contact, and that engineers would be transformed into zombie-like automatons, addicted to their workstations. That hasn't happened; workplace experts say that engineers rely as much as ever on face-to-face interactions.